Human Resource Management in the Educational Institution – Big Changes Ahead - L. V. Kartashova; O. V. Tolstykova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article was devoted to improving the management of human resources in the educational institution. On the basis of Russian and international experience, the main tasks of personnel management in a modern university were considered. Key factors determining peculiarities of personnel work in the university depending on the development strategy, life cycle, priority areas of activity have been identified. Separate proposals have been formulated to strengthen the role of the personnel service in increasing the competitiveness of Russian universities in the international arena. The main reserves of efficiency of personnel work in the university were analyzed. Challenges and opportunities were identified to ensure staff involvement in solving the strategic tasks of the educational institution on the basis of increasing motivation of employees and taking into account their labour contribution to the progressive development of the university. Existing contradictions and problems in assessing the activities of scientific and pedagogical workers and communicating the results of the assessment to the performers were identified. The system of com-plex evaluation of personnel of educational institution is proposed, its goals and tasks are defined. Classifications of objects, subjects and methods of assessment are proposed. The need to apply progressive methods of assessing university personnel on the basis of MBO (management by objectives) using KPI, 360-degree approach, etc., was justified. Directions of personnel evaluation results use in personnel decision-making are defined.